(untitled) (Historia, 2021)
In the 1950's the Afro-Asian nations in the United Nations launched a plan for mandatory sanctions against South Africa, due to the latter's policy of apartheid. In most of the early campaigns, South Africa had enjoyed the support of the United States, although the latter had always verbally condemned the South African Government's policy of apartheid. With the onset of the Kennedy Administration in the United States in 1961, this situation was however due to change.